PERAN MOTIVASI SEBAGAI VARIABEL MEDIASI PADA PENGARUH KUALITAS SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN KOPERASI DI KABUPATEN BADUNG - Anak Agung Gde Alit Wiradyatmika (Jurnal Ilmiah Satyagraha, 2022)
In managing operatives it will require very capable human resources toenable operatives to be able to bring real benefits to the economy. The purpose ofthis study was to determine the effect of the quality of human resources onemployee performance. And knowing the role of motivation on the influence of thequality of human resources on employee performance. This study involved asample of 65 respondents using proportional sampling. The data analysistechnique used SEM-PLS. The results showed that the quality of human resourceshad a positive and significant effect on employee performance. And motivationcan mediate the influence of the quality of human resources on employeeperformance